The Crime of Crimes : Demonology and Politics in France, 1560-1620. - Pearl, Jonathan L. (Wilfrid Laurier University Press, 2006)
One of the most intriguing, and disturbing, aspects of history is that most people in early modern Europe believed in the reality and dangers of witchcraft. Most historians have described the witchcraft phenomenon as one of tremendous violence. In France, dozens of books, pamphlets and tracts, depicting witchcraft as the most horrible of crimes, were published and widely distributed. In his book, The Crime of Crimes: Demonology and Politics in France, 1560-1620, however, Jonathan Pearl shows that France carried out relatively few executions for witchcraft. Through careful research he shows that a zealous Catholic faction identified the Protestant rebels as traitors and heretics in league with the devil and clamoured for the political and legal establishment to exterminate these enemies of humanity. But the courts were dominated by moderate Catholics whose political views were in sharp contrast to those of the zealots and, as a result, the demonologists failed to ignite a major witch-craze in France. Very few studies have taken such a careful and penetrating look at demonology in France. The Crime of Crimes: Demonology and Politics in France, 1560-1620 sheds new light on an important period in the history of witchcraft and will be welcomed by scholars and laypersons alike.